The knowledge requirements of farmers in the field of safe – production for vegetables in (Albayan Scientific Journal, 2023)
The study aims to recognize on the knowledge requirements of farmers in the field of safe vegetables production and on the most obstacles facing them.Date were collected through questionnaire and personal interview during ( March – April ) 2018 from a suessive patron sample of ( 90 ) researched persons.The study has developed a seven measurement farming items with a bindle of better agricultural practices that the farmers have to follow in order  to produce safe food from vegetables, which they are:Crop – composition , sources of fertilizer, improvement of farm conditions, irrigative awareness, plant protection (control) improvement marketing processes, and the ecological behavior of the farmer.Percentage , frequency tables , average, standard devotion, simple correlation, mulity regression and alfa – equation were used statistically. The results cleared that ( 92 % ) of researched individuals are of intensive knowledge requirements for safe vegetables production.The results showed a significant positive relationship between the dependent variable (   knowledge – requirement ) and these independent variables: farm size , attitude to wares the change, farmers attitude to the use of technological approaches, all these at ( 0.05 level ).  This relationship was positive at( 0.01) with: achievement goal, degree of planning in farm management. The results also pointed to a negative significant relationship at  ( 0.01) between the degree of knowledge requirement as and the degree destined of a dependent variable the researched individuals.The results cleared that the variables having significant correlative relationship interpret ( 45 % ) of the variation in dependent variable ( R2 ) 0.456 and this indicates that there are other variables can interpret ( 50 % ) and did not included in the study.The results also demonstrated some obstacles (proplems) which about ( 90 % ) of the researches are faced farmers in the sample study, which  are: absence of marketing knowledge, areas demanded to be cultivated with each crop, the suitable times for cultivation, the average prices, and the absence of marketing system which is taking in regards (the quality, price, the different handling processes),Also the absence of local market that covers  a part of production.The majority of the researches in the sample complains of irrigation water shortage ( quantity and quality ). Most of the researched farmers have the willing to activate the role of agricultural extension in all the previous fields, and to help them choose the best crop combination.